Examining Similarities and Differences among Pharmacy Educational Mobile Applications - Serge Afeli (University of Minnesota Libraries Publishing, 2018)
The use of educational mobile applications (EMAs) to enhance student learning experience is gaining considerable interest across college campuses in the U.S. Some EMAs are more commendable than others because of their ability to effectively help students study lecture materials, learn new concepts, prepare for exams, and improve their overall academic performance. The aim of this commentary is to highlight the major EMAs currently available to pharmacy students while addressing the similarities and differences between them.   Type:  Commentary